If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(s + -2) = 12 Reorder the terms: -7(-2 + s) = 12 (-2 * -7 + s * -7) = 12 (14 + -7s) = 12 Solving 14 + -7s = 12 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -7s = 12 + -14 Combine like terms: 14 + -14 = 0 0 + -7s = 12 + -14 -7s = 12 + -14 Combine like terms: 12 + -14 = -2 -7s = -2 Divide each side by '-7'. s = 0.2857142857 Simplifying s = 0.2857142857
| 3y-5y=-16 | | -201-4x=11x+54 | | -22-8x=12-9x | | -3(3-x)=2x+5 | | r-2(14)=14 | | -21-11x=-13x+29 | | 5n-7=3n+5 | | 2x/5+1=3 | | P=2b+2c | | x-81=-9x+99 | | -15(y+2)=-20 | | 195=r*3 | | x3/3+4x2+22x=0 | | 8x-4-5x=x+7+x | | x3/3+4x2+22x | | 8x-4-5x=x+7+7 | | 24=0 | | 15x+1=24 | | 7x+6=10x+2 | | 10+8x=24 | | 9+6x+2x-1=24 | | xa-H=2ab+C | | 42x-2x^2=0 | | -4+3x=4x-8 | | 3a(6a-5)+4=10 | | 6=w+37 | | 3x-4/2=4 | | 4x-1=-2x+12 | | m+1/2=5 | | 3ax-x= | | 2/3x+5/5x | | 3x+5=-10+x |